A Bayesian Approach to Backtest Overfitting - Jiří Witzany (Charles University in Prague, Institute of Economic Studies (IES), 2017)
Quantitative investment strategies are often selected from a broad class of candidate models estimated and tested on historical data. Standard statistical technique to prevent model overfitting such as out-sample back-testing turns out to be unreliable in the situation when selection is based on results of too many models tested on the holdout sample. There is an ongoing discussion how to estimate the probability of back-test overfitting and adjust the expected performance indicators like Sharpe ratio in order to reflect properly the effect of multiple testing. We propose a consistent Bayesian approach that consistently yields the desired robust estimates based on an MCMC simulation. The approach is tested on a class of technical trading strategies where a seemingly profitable strategy can be selected in the näive approach.
Keywords: G1; G2; C5; G24; C11; C12; C52; 330; Backtest; multiple testing; bootstrapping; cross-validation; probability of backtest overfitting; investment strategy; optimization; Sharpe ratio; Bayesianprobability; MCMC